(3dhGbM GdCfhGQ GdbOSjI aj efGbH GdYdeGA hGdUhajIs - (3YHO GdhgGH Hf CMeO Hf Ydj GdMfaj, fSHg Edj eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO,J (B973 (3g` s
(3ChdgG (B:s
(3CMeO ddg QH GdYGdejf hCTgO Cf dGEdg EdG Gddg Gdedc s
(3hgj GdWHbGJ GdhSWi ai JQGLe GdUhajgs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B218s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B226 s
Keywords: (3GdJGQjNs